2012
DOI: 10.1074/jbc.m111.326538
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Stress Regulates Mammalian Target of Rapamycin (mTOR) Complex 1 via c-Jun N-terminal Kinase (JNK)-mediated Raptor Protein Phosphorylation

Abstract: Background: mTORC1 integrates diverse signals including stress to control cell growth. Results: JNK phosphorylates Raptor, a component of mTORC1, and activates mTORC1 kinase upon osmotic stress. Conclusion: mTORC1 is regulated by JNK during osmotic stress. Significance: Our findings provide the JNK-Raptor relationship as a potential mechanism by which stress activates mTORC1 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
(51 reference statements)
5
34
1
Order By: Relevance
“…6A,B). JNK is suggested to induce Raptor-S863 phosphorylation under strong hyperosmotic stress (Kwak et al 2012). Consistently, we observed that, in Nlk knockout cells, a high concentration of sorbitol could still increase Raptor-S863 phosphorylation, which was blocked by JNK inhibitor (Fig.…”
Section: Nlk Inhibits Mtorc1 By Phosphorylating Raptor S863 Residuesupporting
confidence: 85%
See 4 more Smart Citations
“…6A,B). JNK is suggested to induce Raptor-S863 phosphorylation under strong hyperosmotic stress (Kwak et al 2012). Consistently, we observed that, in Nlk knockout cells, a high concentration of sorbitol could still increase Raptor-S863 phosphorylation, which was blocked by JNK inhibitor (Fig.…”
Section: Nlk Inhibits Mtorc1 By Phosphorylating Raptor S863 Residuesupporting
confidence: 85%
“…For example, AMPK might be activated under stress to inhibit mTORC1 (Chen et al 2010). Phosphatase activation upon hyperosmotic stress might also contribute to S6K dephosphorylation (Parrott and Templeton 1999;Kwak et al 2012). Nevertheless, our result indicates that the compromised mTORC1 inhibition, not activation of phosphatase, is responsible for the altered S6K phosphorylation in the Nlk knockout cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations